Inoculation methods of Sclerotinia sclerotiorum for screening of soybean cultivars resistant to white mold - Garcia, Riccely Ávila; Meyer, Maurício Conrado; Ávila, Kássia Aparecida Garcia Barbosa; da Cunha, Marcos Gomes (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the efficacy and usefulness of methods of Sclerotinia sclerotiorum inoculation for screening soybean cultivars resistant to white mold. Four inoculation methods were evaluated in plants at the V3/V4 phenological stages. Stem lesion length was measured three and seven days after inoculation. The soybean cultivars BRS 8460RR, BRSGO Ipameri, and P98Y11 had the smallest stem lesions. The inoculation method with pipette tip on the petiole is the most effective and practical to evaluate soybean resistance to white mold.